2014
DOI: 10.1021/ol5028392
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Stereocontrolled Synthesis of 1,2,4-Trioxolanes Useful for Ferrous Iron-Dependent Drug Delivery

Abstract: Ferrous iron-promoted reduction of a hindered peroxide bond underlies the antimalarial action of the 1,2,4-trioxane artemisinin and the 1,2,4-trioxolane arterolane. In appropriately designed systems, a 1,2,4-trioxolane ring can serve as a trigger to realize ferrous iron-dependent and parasite-selective drug delivery, both in vitro and in vivo. A stereocontrolled, expeditious (three steps), and efficient (67–71% overall yield) synthesis of 1,2,4-trioxolanes possessing the requisite 3″ substitution pattern that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…A nonperoxidic dioxolane conjugate ( 3 ) was also prepared to confirm that the cytotoxicity of 1 is ablated in conjugated forms and that intracellular release of active 1 from 2 is peroxide-dependent (Figure 2a and Figure S2). Finally, trioxolane analog 4 (29) lacking the microtubule toxin was prepared to control for intrinsic cytotoxicity of the TRX moiety (Figure 2a). The cytotoxicity of the trioxolane-conjugate 2 and control compounds 1 , 3 , and 4 was then assessed across a small panel of cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A nonperoxidic dioxolane conjugate ( 3 ) was also prepared to confirm that the cytotoxicity of 1 is ablated in conjugated forms and that intracellular release of active 1 from 2 is peroxide-dependent (Figure 2a and Figure S2). Finally, trioxolane analog 4 (29) lacking the microtubule toxin was prepared to control for intrinsic cytotoxicity of the TRX moiety (Figure 2a). The cytotoxicity of the trioxolane-conjugate 2 and control compounds 1 , 3 , and 4 was then assessed across a small panel of cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…17,20 Given that labile Fe(II) promotes Fenton chemistry, we sought to develop a tumor-targeting strategy in which Fenton reaction of a peroxidic prodrug was coupled to release of drug payloads. Recognizing that antimalarial agents such as arterolane 2124 exhibit finely tuned iron(II) reactivity, 2528 we subsequently developed 29,30 an arterolane-inspired small molecule platform (denoted TRX herein) for Fe(II)-dependent drug delivery. These TRX-drug conjugates function via initial Fe(II)-promoted fragmentation of a 1,2,4-trioxolane ring to afford a cyclohexanone intermediate, followed by spontaneous β-elminiation and decarboxylation to release the drug payload (Figure 1 and Supporting Information Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…In ICL-1, we caged D-aminoluciferin with an Fe 2+ -reactive endoperoxide trigger (15,17,51) inspired by antimalarial agents that exhibit Fe 2+ -dependent pharmacology (52,53). ICL-1 was designed to undergo metal-and redox-specific Fe 2+ -dependent cleavage to generate D-aminoluciferin, which can interact with the firefly luciferase enzyme to produce red light output through a catalytic bioluminescent reaction.…”
Section: Significancementioning
confidence: 99%
“…As we recently reported, trans-5 is available from 3-hydroxycyclohexanone in a three-step process involving a diastereoselective Griesbaum co-ozonolysis reaction as the key step. 16 While this same process can yield single enantiomers of 5 when starting from non-racemic 3-hydroxycyclohexanone, (±)-5 was employed for the studies reported herein. In a similar fashion, we prepared the conjugate 6 16 to explore the effects of 3"-carbamate substitution in a trioxolane analog more closely related to 2.…”
Section: Scheme 1 Trioxolane-mediated Release Of Mefloquine From Trimentioning
confidence: 99%